Por sua culpa, sua tão grande culpa : um estudo sobre o processo de naturalização, responsabilização e culpabilização das mães dos meninos e meninas em situação de rua - Oliveira, Everaldo Santos (2015)
This research makes an analysis of the process of accountability of mothers of children and adolescents living on the streets, abandonment context in which their children are. The presence of children and adolescents living on the streets of our cities constitutes one of the cruelest expressions of social inequality that affects our country. This phenomenon is not new in the history of Brazil, and even with the economic, social and legal advances in recent decades, continues to exist. Several scientific studies have been conducted on this topic, however, there is a prevalence in these theoretical debates a discussion of the various factors causing this phenomenon and care to this population policies. In conceptual and empirical field we did not find a deeper reflection on the importance of the mother of the boys and girls on the streets as provider affective, moral and material in the lives of their children and the whole family. This thesis aims to develop an analysis of the naturalization process and accountability of the roles socially assigned to the family institution, more specifically the mother figure in the material and emotional care of their children, and the consequent "blame" those mothers who, for various reasons, do not correspond to moral, social and legal imposed by various segments of society. This study also sought to analyze the mother figure of perspective, the reasons why your child to get the experience of living on the street. The methodological process is based on the socio-historical analysis of conceptual approaches on family, gender, race / ethnicity, deepening the different theme determinations addressed in relation to children, adolescents and their families. We conducted a case study based on the analysis of the life stories of three women mothers of young people on the streets, interviewed for this search. Through these analyzes it was possible to realize how much these individual reports are organized around certain individual and collective events, moving beyond the merely subjective character. The categorization and analysis of the speeches of the people-subject took into consideration the fact that in quantitative research data collection occurs in a context fluent relations in the interactive process with the subjects, in order to reach its essence. Opting for this type of research is rightly given the fact that it encourage respondents to think freely about any subject, object, or concept, which allowed researchers to access objective aspects, but also subjective, of respondents spontaneously. From the analysis and discussion of the data it can be said that despite all the adversities and misunderstandings that mark the lives of these women, they are those who take on the difficult task of being the mainstay of the family and the primary affective and moral reference for your children